ANALYSIS OF PUBLIC SAFETY CENTER 119 AMBULANCE SERVICES USING LEAN SIX SIGMA - Rojak, Thasya Sabilla Putri; Basabih, Masyitoh; Winarto; Suranta, Roy Michael (Universitas Airlangga, 2024)
Background: DKI Jakarta reports about 5,000 annual deaths from heart disease, disasters, accidents, and other causes. Ambulance demand has risen, especially for COVID-19 cases that require quick medical attention. In 2022, the average emergency response time was 21-30 minutes. Therefore, efforts are needed to improve the response time of PSC 119 ambulances to minimize impacts. Aims: This study uses the Lean Six Sigma methodology to analyze the factors contributing to prolonged response times in emergency ambulance services. Methods: This study used a mixed-method approach based on the DMAI (define, measure, analyze, and improve). The data were collected through observations, document reviews, and in-depth interviews. Results: The results showed that the average duration of ambulance services was 4 hours and 30 minutes. The identified inefficiencies include software issues with the Nusantara app, staff fatigue, and license renewals, difficult access for ambulance and URC units, delays from call center staff awaiting family decisions, closely located posts leading to fewer cases per post, community-initiated patient movements, challenges in finding suitable referral hospitals for special cases, and slow response times from referral hospitals. Conclusion: The recommended improvements include using a kaizen board, conducting expert training, promoting the Integrated Referral System or Sistem Informasi Rujukan Terintegrasi (SISRUTE), and revising standard operating procedures. Keywords: ambulance services, Public Safety Center 119, Lean Six Sigma